Changes in Time Spent Outdoors During the Daytime in Rural Populations in Four Geographically Distinct Regions in China: A Retrospective Study. (28th February 2017) - Gao, Qian; Wang, Fang; Hu, Liwen; Yu, Jiaming; Liu, Rong; Wang, Yang; Liu, Yang
Abstract: Changes in time‐activity patterns may influence personal exposure to various environmental factors and affect individual health. However, few studies have investigated the changes in patterns of time spent outdoors. To investigate the trends in outdoor activity in recent decades in China, a retrospective questionnaire was used to examine the amount and pattern of time spent outdoors during the day by 2076 subjects in four geographically distinct rural regions of China. Rural Chinese people spent less time outdoors than they used to because of the economic development, increase in education and changes in working conditions that occurred over time. Outdoor time was the shortest during the school stage of life (Sanya: 3.24–3.61; Shaoxing: 3.35–3.68; Lhasa: 4.37–4.54; Xiuyan: 2.94–3.26 h per day). Subjects in wealthy regions spent less time outdoors during their working stage of life. In the four regions in this study, the average daily times spent outdoors were 3–13% lower for subjects aged 40–59 years and 20–38% lower for those under 40 years compared to subjects aged 60 years and over. Certain health‐related issues, such as vitamin D deficiency, will become more prominent in China if this trend continues. Abstract : This study investigated the amount and pattern of time spent outdoors during the day by 2076 subjects in four geographically distinct rural regions in China. The average daily hours spent outdoors were 3–13% lower for subjects aged 40–59 years and 20–38% lower for those under 40 years compared to subjects aged 60 years and over. Outdoor time was the shortest during the school stage of life. The greatest decrease in time spent outdoors occurred between the young group and the old group during the work stage.